Uncovering shared genetic features between inflammatory bowel disease and systemic lupus erythematosus - Vikram R. Shaw; Jinyoung Byun; Catherine Zhu; Rowland W. Pettit; Jeffrey M. Cohen; Younghun Han; Christopher I. Amos (Scientific Reports)
Abstract Inflammatory bowel disease (IBD) is an autoimmune disease (AD) characterized by chronic, relapsing intestinal inflammation. Systemic lupus erythematosus (SLE) is a complex autoimmune disease with multisystem involvement and overactivation of both innate and adaptive immunity. The extra intestinal manifestations (EIMs) that commonly occur in IBD include many of the organ sites that are affected by SLE. ADs are often comorbid with one another and may have shared underlying genetic features and architectures contributing to their pathogenesis and disease course. We performed both epidemiological and post-genome wide association study (GWAS) analyses to investigate the shared genetic features between IBD and systemic lupus erythematosus (SLE). Specifically, we performed epidemiological association analysis in the All of Us Research Program (AoURP) and genome-wide/local genetic correlation analysis and cell-type specific SNP heritability enrichment analysis using previously published summary level data. A significant epidemiologic association exists between IBD and SLE with an adjusted odds ratio (aOR) of 2.94 (95% CI: 2.45–3.53; P < 0.001) in a multivariable model accounting for confounders in the AoURP data. Genome-wide genetic correlation analysis in previously published summary level data demonstrated a significant genetic correlation between IBD, CD, and UC with SLE, and local genetic correlation analysis demonstrated several positive and significant correlations in local genomic regions harboring disease variants in genes common to both SLE and IBD etiology, including variants in ELF1, CD226, JAZF1, WDFY4, and JAK2. Cell-type SNP heritability enrichment analysis identified both overlapping and distinct functional categories contributing to SNP heritability across IBD phenotypes. Notably, IBD-related phenotypes demonstrated significant enrichment in T-lymphocyte functional groups while SLE signal appeared in distinct categories, such as B-lymphocytes (along with CD). Gene-level collapsing analysis of rare variants in the United Kingdom BioBank (UKBB) identified overlapping nominally-significant genes between SLE and IBD, CD, and UC. By leveraging several post-GWAS methods, the present study identifies shared genetic features between IBD and SLE, highlighting similarities and differences in the genetic features that contribute to the pathogenesis of each disease.